2019
DOI: 10.3390/bioengineering6010025
|View full text |Cite
|
Sign up to set email alerts
|

Data Integration and Interoperability for Patient-Centered Remote Monitoring of Cardiovascular Implantable Electronic Devices

Abstract: The prevalence of cardiovascular implantable electronic devices with remote monitoring capabilities continues to grow, resulting in increased volume and complexity of biomedical data. These data can provide diagnostic information for timely intervention and maintenance of implanted devices, improving quality of care. Current remote monitoring procedures do not utilize device diagnostics to their potential, due to the lack of interoperability and data integration among proprietary systems and electronic medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Currently, patients do not receive information directly from their remote monitored device, which patients in this study pointed out as a downside. However, findings from a feasibility [ 42 ] and evaluation [ 20 ] study in the United States suggest that it is not only feasible to deliver data from remote monitoring directly to patients, but also that this data sharing does not adversely impact clinic workflow and that patients perceive a benefit from having access to their remote monitoring data. The same result was found by Mirro et al when evaluating the impact of sharing ICD data summaries through a patient portal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, patients do not receive information directly from their remote monitored device, which patients in this study pointed out as a downside. However, findings from a feasibility [ 42 ] and evaluation [ 20 ] study in the United States suggest that it is not only feasible to deliver data from remote monitoring directly to patients, but also that this data sharing does not adversely impact clinic workflow and that patients perceive a benefit from having access to their remote monitoring data. The same result was found by Mirro et al when evaluating the impact of sharing ICD data summaries through a patient portal.…”
Section: Discussionmentioning
confidence: 99%
“…For example, some patients (5%-22%) do not feel comfortable with RPM and report a strong preference for regular office-based visits to feel secure [ 15 , 16 ]. Furthermore, RPM has been described as system centered, providing patients with little or no data from their device [ 20 ]. Patients missed receiving feedback via their monitor, 84% wished for a more detailed response, and 21% wished for faster feedback after scheduled transmissions [ 16 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed in the PGHD Accessibility section, depending on the health condition and the clinical purpose of RPM, PGHD presentation to patients in real time might be deliberately disabled by clinicians. However, studies have shown that accessing real-time data from the wearable increased patients' awareness of the wearable's function, further engaged them in self-care, and enhanced shared decision-making [92][93][94].…”
Section: Recommendation 17: Pghd From Wearables Should Be Available T...mentioning
confidence: 99%
“…The primary goals of this pilot study were to gain insight into individual patients’ interpretations of device data and visualizations and their responses to RM data in daily life, and to contribute these insights to an emerging field of health data sharing that ultimately aims to design and implement technologies to further engage patients safely and effectively in self-management. 16 , 23 , 24 , 25 …”
Section: Introductionmentioning
confidence: 99%